INCIDENCE OF FUNGI IN MOMBASA GRASS SEEDS DURING THE STAGES OF THE SEED CONDITIONING PROCESS - Silva, Givanildo Z. da; Martins, Cibele C. [UNESP]; Melo, Lilian F. de; Jeromini, Tatiane S. [UNESP]; Panizzi, Rita de C. [UNESP] (Soc Brasil Engenharia Agricola, 2019)
The objective of this study was to evaluate the effect of the seed conditioning process on the sanitary quality of Panicum maximum 'Mombasa' seeds. The seeds were sampled before processing and after exiting the seed blower and sieves (discharge from the top and bottom sieves), first gravity separator (intermediate discharge), seed treatment equipment (dyeing the seeds of the intermediate discharge from the first separator), and second gravity separator (upper, intermediate, and lower discharge). Sanitary analysis was performed by the Blotter Test method with and without surface disinfestation of the seeds, which were incubated at 20 +/- 2 degrees C, with a photoperiod of 12 h, for 7 d. The conditioning process increased the incidence of Fusarium sp. in the Mombasa grass seeds. In addition, Cladosporium sp. and Alternaria sp. were found in and on the surface of the seeds and, therefore, can be disseminated by the seed conditioning machines. The percentage of seeds with Alternaria sp. decreased after dyeing and after the top discharge of the second gravity separator stage.
Keywords: seed pathology; processing; seed sanitation; Panicum maximum 'Mombasa'